2024
DOI: 10.1002/mc.23673
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide mononucleotide induces autophagy and ferroptosis via AMPK/mTOR pathway in hepatocellular carcinoma

Zhanbo Sun,
Lixian Liu,
Hongyuan Liang
et al.

Abstract: Hepatocellular carcinoma (HCC) is a common malignancy worldwide. Herein, we investigated the role of nicotinamide mononucleotide (NMN) in HCC progression. HCC cells were treated with NMN (125, 250, and 500 μM), and then nicotinamide adenine dinucleotide (NAD+) and NADH levels in HCC cells were measured to calculate NAD+/NADH ratio. Cell proliferation, apoptosis, autophagy and ferroptosis were determined. AMPK was knocked down to confirm the involvement of AMPK/mTOR signaling. Furthermore, tumor‐inhibitory effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(121 reference statements)
1
0
0
Order By: Relevance
“…36,37 Multiple studies have demonstrated increased NAD + /NADH ratios after NMN intervention. 38,39 Our findings agree that a pathway likely exists between p53 and NMN, as represented by NMNAT2/NMNAT3 → NAD + → AMPK → SIRT1 → p53; studies suggest that NMNAT2 and NMNAT3 are the primary regulatory factors in this process. Interestingly, the study identified NMNAT2 as a new downstream target gene of p53 40 and speculated that there may be a feedback loop between p53 and NAD + .…”
Section: Papersupporting
confidence: 79%
“…36,37 Multiple studies have demonstrated increased NAD + /NADH ratios after NMN intervention. 38,39 Our findings agree that a pathway likely exists between p53 and NMN, as represented by NMNAT2/NMNAT3 → NAD + → AMPK → SIRT1 → p53; studies suggest that NMNAT2 and NMNAT3 are the primary regulatory factors in this process. Interestingly, the study identified NMNAT2 as a new downstream target gene of p53 40 and speculated that there may be a feedback loop between p53 and NAD + .…”
Section: Papersupporting
confidence: 79%